2016
DOI: 10.1016/j.geoderma.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Linking short-term soil carbon and nitrogen dynamics: Environmental and stoichiometric controls on fresh organic matter decomposition in agroecosystems

Abstract: 21A continuous, nonlinear model (FLOG-CN) linking carbon mineralization and nitrogen 22 mineralization-immobilization with respect to time was developed that successfully reproduced 23 the complex CO 2 -C and SMN dynamics for a collection of 70 paired C and N soil datasets. 24 Application of the model to diverse C and N datasets showed that incorporating latency into the 25 model of C mineralization, and using C to drive N dynamics, allows heterogeneous data from 26 many different soil amendments to be des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Nonetheless, Parton et al (2007) observed net N release when litter mass loss arrived at 60% and the average C/N ratio was lower than 40 in a 10-year field decomposition experiment. These inconsistent findings about C/N threshold for net N mineralization could be attributed to the differences in experimental conditions and duration, and also to the residue C and N characteristics (Abiven et al, 2005;Jensen et al, 2005;Gillis and Price, 2016). Trinsoutrot et al (2000b) reported that the quantity of N released from roots, stems, and pod walls of Brassica napus L. were closely related to the initial N content.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, Parton et al (2007) observed net N release when litter mass loss arrived at 60% and the average C/N ratio was lower than 40 in a 10-year field decomposition experiment. These inconsistent findings about C/N threshold for net N mineralization could be attributed to the differences in experimental conditions and duration, and also to the residue C and N characteristics (Abiven et al, 2005;Jensen et al, 2005;Gillis and Price, 2016). Trinsoutrot et al (2000b) reported that the quantity of N released from roots, stems, and pod walls of Brassica napus L. were closely related to the initial N content.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, alternative methods can be used to define manure pools kinetically. They assign C and N contents to model pools that optimize the simulation of experimental dynamics (Gillis & Price, ; Mondini et al, ; Noirot‐Cosson et al, ; Petersen et al, ) and assume implicitly that fast‐ and slow‐decay pools are chemically heterogeneous mixtures of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Previous aerobic incubation studies (Bechini & Marino, ; Morvan, Nicolardot, & Péan, ; Thomsen & Olesen, ) have shown the complexity of responses related to C respiration and N immobilization in manure‐amended soils. The suitability of simulation models to reproduce, through adequate model parameterization, C and N decomposition dynamics after manure incorporation has also been shown to be difficult (Cavalli & Bechini, ; Gillis & Price, ; Petersen et al, ; Probert et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of C and N are largely linked via the chemical composition and stoichiometry of biomolecules (Gillis and Price, 2016). The unique relationship between the total N and the total OC implies that both reveal similar general trends of accumulation, degradation and subsurface transport, and hence, always follows similar patterns (Wong et al, 2008 andSharma et al, 2017).…”
Section: Soil Nitrogen Stock (Sns)mentioning
confidence: 99%